Panmixia in a sea ice-associated marine mammal: evaluating genetic structure of the Pacific walrus (Odobenus rosmarus divergens) at multiple spatial scales - Beatty, William; Lemons, Patrick; Sethi, Suresh; Everett, Jason; Lewis, Cara; Lynn, Robert; Cook, Geoffrey; Garlich-Miller, Joel; Wenburg, John (Zenodo, 2020)
The dataset includes 5303 Pacific walrus genotypes for 114 single nucleotide polymorphisms used in the manuscript "Panmixia in a sea ice-associated marine mammal: evaluating genetic structure of the Pacific walrus ( Odobenus rosmarus divergens ) at multiple spatial scales". Biopsy samples were collected from Pacific walruses hauled-out on sea ice in the Bering and Chukchi seas from 2013-2017 in June of each year. Genotypes are presented in two columns per locus and missing data is coded as "N".